A method for detecting copper content of copper powder recovered from negative electrode by crushing

CN122882674APending Publication Date: 2026-10-09安徽巡鹰新材料科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611060065.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-16
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种负极回收破碎铜粉的铜含量检测方法,解决现有技术检测方法中检测误差大、操作繁琐的问题

Benefits of technology

(1)本发明采用圆锥四分法取样,可充分混匀负极回收破碎铜粉物料,有效规避因铜粉粒径差异、杂质分布不均引发的取样偏析问题,保障所取样品具备充分代表性,从检测源头消除取样环节引入的系统性误差。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a copper content detection method for negative electrode recovery broken copper powder and belongs to the technical field of batteries. The application guarantees representativeness through conic four-part sampling, implements differential pretreatment according to impurity and particle size difference, simplifies low-impurity sample process, and strengthens impurity removal of high-impurity samples. Through ammonia-acetic acid buffer system control pH to inhibit interference, and optimization of the adding time of masking agent, indicator and potassium thiocyanate in iodimetry titration, the problems of uneven sampling, impurity interference, process mismatch and end point insensitivity are effectively solved, and accurate, rapid and stable determination of the copper content of the negative electrode recovery copper powder is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and specifically to a method for detecting the copper content in recovered crushed copper powder from a negative electrode. Background Technology

[0002] The recovered crushed copper powder originates from the recycling process of negative electrode materials from waste lithium-ion batteries. Its composition is complex, typically containing various non-metallic and metallic impurities such as graphite, aluminum foil fragments, and separator residues. The copper content of this type of copper powder fluctuates significantly, and the particle size distribution is uneven, posing special requirements for conventional copper content detection methods in terms of sample pretreatment, representative sampling, and interference elimination.

[0003] Currently, the detection of copper-containing materials mainly employs methods such as iodometric titration, EDTA titration, atomic absorption spectrometry, or X-ray fluorescence analysis. Among these, iodometric titration is widely used in industrial settings and laboratories for determining copper content due to its simplicity, low cost, and wide applicability. However, existing technologies still have limitations in handling copper powder with complex compositions, high impurity content, and uneven particle size.

[0004] Patent CN115598287A discloses a method for detecting copper content in conductive pastes. This method involves first removing organic matter, then digesting the metal mixture with strong acid and an oxidizing agent, and finally performing titration analysis. This method features a pretreatment process designed for conductive pastes containing organic binders, effectively solving the problem of interference from organic matter in subsequent measurements. However, this method is mainly geared towards liquid or semi-solid paste systems. While its pretreatment conditions (such as high-temperature ashing and strong acid digestion) can remove organic matter, it lacks specific treatment measures for insoluble solid impurities such as graphite and membranes commonly found in copper recovery from negative electrodes. Furthermore, it does not consider the segregation of different particle sizes during sampling, which may affect the repeatability and accuracy of the final test results.

[0005] Existing technologies still have room for improvement in the removal of solid impurities, representative sampling, and optimization of the applicability of iodometric titration when processing samples such as crushed copper powder from negative electrode recovery, which are characterized by high impurities, wide particle size distribution, and large compositional fluctuations. There is an urgent need for a copper content detection method specifically designed for the characteristics of such materials to improve detection efficiency and result reliability. Summary of the Invention

[0006] The purpose of this invention is to provide a method for detecting the copper content of recovered crushed copper powder from a negative electrode, thereby solving the problems of large detection errors and cumbersome operation in existing detection methods.

[0007] The objective of this invention can be achieved through the following technical solutions: A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: S1. Obtain the required sample amount using the conical quartering method and distinguish the samples; S2. The sample is pretreated to obtain a pretreated sample solution; S3. Add ammonia solution to the pretreated sample solution until a blue precipitate appears, then add acetic acid solution until the precipitate dissolves, and then add 1 mL of acetic acid solution to obtain the acidified sample solution. S4. Add ammonium bifluoride and potassium iodide to the acidified sample solution in sequence, and then titrate with 0.1 mol / L sodium thiosulfate standard solution. When the solution color changes from bright yellow to pale yellow, add 5 g / L starch indicator, and the solution turns blue. Continue titrating until the blue color is about to disappear, then add 10 wt% potassium thiocyanate solution, and the solution turns blue again. Continue adding sodium thiosulfate standard solution until the blue color completely disappears, which is the titration endpoint. Record the amount of sodium thiosulfate standard solution consumed and calculate the copper content.

[0008] Furthermore, the differentiation method includes the following: If the total proportion of solid impurities such as graphite, diaphragm, and aluminum particles in the sample is less than 5%, and more than 90% of the particles can pass through a 75μm standard sieve, then it is a low-impurity fine particle sample. If the impurity percentage in the sample is higher than 5%, or if there are obvious unbroken aluminum flakes or membrane fibers, and more than 30% of the particles are retained on the 75μm sieve, then it is a high-impurity coarse particle sample.

[0009] Impurities <5% and 90% passing through a 75μm sieve indicate high sample homogeneity, requiring only basic dissolution; conversely, the presence of unbroken hard impurities (such as aluminum flakes) necessitates deep impurity removal. This classification ensures that the pretreatment intensity accurately matches the actual contamination level of the sample, avoiding overtreatment of low-impurity samples leading to copper loss or undertreatment of high-impurity samples causing interference.

[0010] Furthermore, the pretreatment of the low-impurity fine-particle sample includes the following steps: Take a low-impurity fine particle sample, add 6 mol / L dilute hydrochloric acid and 30 wt% hydrogen peroxide, heat to 80~90℃ and react for 5~10 min, then rapidly heat to 150℃ until no tiny decomposition bubbles are visible, then cool to 24~26℃.

[0011] Rapidly raise the temperature to 150°C until no tiny decomposition bubbles remain, and remove excess hydrogen peroxide. If the hydrogen peroxide is not completely removed, the titration result will be too high.

[0012] Furthermore, the ratio of the sample, dilute hydrochloric acid, and hydrogen peroxide is 0.1~0.3g:3~5mL:3~5mL, wherein the ratio of dilute hydrochloric acid to hydrogen peroxide is 1:1.

[0013] To reduce the amount of acid used by a small proportion, prevent excessive acid adjustment in the later stage that could lead to pH loss; to adapt to low-impurity systems, avoid the introduction of additional ions by excessive reagents that could interfere with the titration reaction.

[0014] Furthermore, the pretreatment of the high-impurity coarse-particle sample includes the following steps: Take a high-impurity coarse particle sample, add 6 mol / L dilute hydrochloric acid and 30 wt% hydrogen peroxide, heat to 85~95℃ and react for 10~15 min, then rapidly heat to 150℃ until no small decomposition bubbles are visible, cool to 24~26℃, make up to 250 mL, filter with an aqueous filter membrane and collect the filtrate, then transfer 10 mL of the filtrate to a 250 mL Erlenmeyer flask.

[0015] Furthermore, the ratio of the sample, dilute hydrochloric acid, and hydrogen peroxide is 2.8~3.2g:18~22mL:18~22mL, wherein the ratio of dilute hydrochloric acid to hydrogen peroxide is 1:1.

[0016] High acid concentration ensures that insoluble impurities (such as aluminum) react fully, while excess acid inhibits the hydrolysis of aluminum ions; the reagent ratio is matched with the impurity load to avoid insufficient treatment leading to residual interfering ions.

[0017] Furthermore, the ammonia solution is prepared by mixing 25 wt% ammonia water and distilled water at a volume ratio of 1:1. This reduces alkalinity to prevent the formation of a stable copper-ammonia complex ([Cu(NH3)4)). 2+ This ensures that copper ions are completely released during subsequent acidification; at the same time, it prevents localized over-alkaliness from causing impurities to co-precipitate.

[0018] Furthermore, the acetic acid solution is prepared by mixing glacial acetic acid and distilled water at a volume ratio of 1:1. This forms an acetic acid-acetate buffer system, precisely maintaining a pH of 3.5–4.0; this range inhibits Fe... 3+ / Al 3+ Hydrolysis interference is mitigated, while ensuring complete precipitation of cuprous iodide (CuI) and optimizing the stoichiometric relationship of the titration reaction.

[0019] Furthermore, the amount of ammonium bifluoride used is 0.5g. Sufficient F - Complex Al 3+ / Fe 3+ (Forming [AlF6]) 3- To eliminate the interference of impurities on the iodometric method; to avoid excessive corrosion of glassware or the introduction of fluoride ion side reactions within the dosage range.

[0020] Furthermore, the amount of potassium iodide used is 1.4~1.6g. Ensure Cu 2+ Completely reduced to Cu + (2Cu) 2+ +4I - →2CuI↓+I2), excess I - Maintaining I2 solubility and preventing iodine volatilization; insufficient dosage will lead to incomplete reaction, while excessive dosage has no negative impact.

[0021] Furthermore, the amount of the 5 g / L starch indicator used is 1.8~2.2 mL. This optimizes the iodine-starch colorimetric sensitivity, avoiding excessive adsorption and endpoint tailing caused by excessively high concentrations; the dosage is precisely matched to the titration system to ensure clear and identifiable blue abrupt changes.

[0022] Furthermore, the amount of the 10wt% potassium thiocyanate solution used is 9-11 mL. Near the endpoint, I2 adsorbed by CuI is added to displace it, allowing the blue color to reappear; insufficient addition will not provide sufficient displacement, while excessive addition may introduce new interferences. This range ensures a sharp endpoint without residual effects.

[0023] Furthermore, the formula for calculating the copper content is as follows: For a low-impurity, fine-particle sample, the copper mass fraction ω(Cu) = (V × c × M × 10) -3 ) / m×100%; For high-impurity coarse-particle samples, the copper mass fraction ω(Cu) = (V × c × M × 10) -3 ×25) / m0×100%; Where V is the volume of sodium thiosulfate standard solution consumed, C is the concentration of sodium thiosulfate standard solution (mol / L), M is the molar mass of copper 63.55 g / mol, m is the mass of the low-impurity fine particle sample (g), and m0 is the mass of the high-impurity coarse particle sample (g).

[0024] Furthermore, the ammonia solution is added until a stable blue flocculent precipitate just appears. Excess ammonia will cause the formation of a copper-ammonia complex, affecting subsequent acidification. The amount of acetic acid solution added is limited to just dissolving the precipitate and being 1 mL in excess, ensuring that the pH of the solution is stable at 3.5 to 4.0. This range can effectively suppress the interference of coexisting ions such as iron and aluminum, while ensuring complete precipitation of cuprous iodide.

[0025] Furthermore, after the potassium iodide is added, titration should begin within 30 seconds to prevent iodine volatilization and loss; the starch indicator should be added at the pale yellow stage to avoid premature addition which would cause the starch-iodine complex to be over-adsorbed and result in a tailing effect at the endpoint; and the potassium thiocyanate should be added near the endpoint to displace the iodine adsorbed on the surface of cuprous iodide, making the endpoint more acute.

[0026] Furthermore, the aqueous filter membrane is a 0.4μm aqueous microporous filter membrane. Before use, the filtration device needs to be rinsed with the solution to be tested to prevent the concentration of the solution to be tested from being diluted.

[0027] The beneficial effects of this invention are: (1) The present invention adopts the cone quartering method for sampling, which can fully mix the negative electrode recovered broken copper powder material, effectively avoid the sampling segregation problem caused by the difference in copper powder particle size and uneven distribution of impurities, and ensure that the sample taken is sufficiently representative, thus eliminating the systematic error introduced by the sampling process from the source of detection.

[0028] (2) Based on the sample impurity content and particle size characteristics, the present invention implements differentiated pretreatment. For low-impurity fine particle samples, the operation process is simplified, the processing time is shortened and the detection efficiency is improved. For high-impurity coarse particle samples, the dissolution and separation steps are strengthened to effectively remove interfering impurities such as graphite, aluminum sheets and membrane fibers, ensure the purity of the pretreated sample solution and avoid the interference of impurity residues on the subsequent titration reaction.

[0029] (3) The present invention adjusts the pH by using an ammonia-acetic acid buffer system. First, ammonia is added dropwise until a blue precipitate appears, and then acetic acid is added dropwise until the precipitate dissolves and there is an excess of 1 mL. This can accurately stabilize the pH of the solution in the optimal range for the iodometric reaction, which can suppress the side reactions of coexisting ions such as iron and aluminum, and ensure that the redox reaction between copper ions and potassium iodide is carried out completely, thus laying a stable chemical environment for accurate titration.

[0030] (4) In this invention, ammonium fluoride and potassium iodide are added sequentially to the acid-adjusting sample solution. Ammonium fluoride can further mask the trace interfering ions remaining in the sample and eliminate their influence on the formation and titration of iodine. Potassium iodide can react quickly with copper ions to generate cuprous iodide precipitate and iodine. The timely addition of reagents can reduce the loss of iodine volatilization and ensure the accuracy of the reaction stoichiometric relationship.

[0031] (5) By optimizing the timing of sodium thiosulfate titration and reagent addition, the present invention adds starch indicator when the solution changes from bright yellow to pale yellow, avoiding the problem of endpoint tailing caused by excessive adsorption of starch-iodine complex due to premature addition; and adds potassium thiocyanate solution when the blue color is about to disappear, which can displace the iodine adsorbed on the surface of cuprous iodide precipitate, making the color change of the titration endpoint obvious and accurate, and greatly reducing human reading error. Detailed Implementation

[0032] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below.

[0033] Example 1 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: After thoroughly mixing the copper sample to be processed, pile it into a cone shape. Use a clean plate to flatten the top of the cone until the thickness is uniform. Then use a cross-shaped sample divider to divide the sample into 4 equal parts. Discard the two diagonally opposite parts. Mix the remaining two parts again and repeat the above operation until the sample amount that meets the experimental requirements is obtained. The total proportion of solid impurities such as graphite, diaphragm, and aluminum particles in the sample is less than 5%, and more than 90% of the particles can pass through a 75μm standard sieve, which is a low-impurity fine particle sample. Weigh 0.2g of sample and place it in a 250mL Erlenmeyer flask. Add 4mL of 6mol / L dilute hydrochloric acid and 4mL of 30wt% hydrogen peroxide to the Erlenmeyer flask. Heat to 85℃ and keep warm for 8min. Then, rapidly heat to 150℃ until there are no small decomposition bubbles. Cool to 25℃ to obtain the pretreated sample solution. Add ammonia solution (V) dropwise to the conical flask containing the pretreated sample solution. 25wt%氨水 V 蒸馏水 =1:1), manually shake, add the corresponding solution dropwise while observing the phenomenon in the conical flask, and after the blue precipitate appears, add acetic acid solution dropwise (V 冰醋酸 V 蒸馏水 =1:1), continue shaking until the precipitate is completely dissolved, then add 1 mL of acetic acid solution, and add distilled water to the conical flask until the solution volume is 100 mL to obtain the acid-adjusted sample solution; Add 0.5 g ammonium bifluoride and 1.5 g potassium iodide to the acidified sample solution. Immediately titrate with 0.1 mol / L sodium thiosulfate standard solution. After the solution changes from bright yellow to pale yellow, add 2.0 mL of 5 g / L starch indicator, and the solution turns blue. Continue titrating with 0.1 mol / L sodium thiosulfate standard solution until the blue color is about to disappear. Add 10 mL of 10 wt% potassium thiocyanate solution to make it turn blue again. Continue titrating with 0.1 mol / L sodium thiosulfate standard solution until the blue color completely disappears, which is the titration endpoint. Record the amount of sodium thiosulfate standard solution consumed and calculate the copper content.

[0034] Example 2 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this embodiment and Example 1 is that the sample is 0.1g, the dilute hydrochloric acid is 3mL, the hydrogen peroxide is 3mL, the stirring temperature is 80℃ for 5min, and the temperature is kept at 90℃ for 3min. The other raw materials and preparation process are the same as in Example 1.

[0035] Example 3 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this embodiment and Example 1 is that the sample is 0.3g, the dilute hydrochloric acid is 5mL, the hydrogen peroxide is 5mL, the stirring temperature is 90℃ for 10min, and the temperature is kept at 98℃ for 5min. The other raw materials and preparation process are the same as in Example 1.

[0036] Example 4 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this embodiment and Example 1 is that the amount of potassium iodide is 1.4g, the amount of starch indicator is 1.8mL, and the amount of potassium thiocyanate is 9mL. The remaining raw materials and preparation process are the same as in Example 1.

[0037] Example 5 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this embodiment and Example 1 is that the amount of potassium iodide is 1.4g, the amount of starch indicator is 2.2mL, and the amount of potassium bisulfate is 11mL. The remaining raw materials and preparation process are the same as in Example 1.

[0038] Example 6 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: After thoroughly mixing the copper sample to be processed, pile it into a cone shape. Use a clean plate to flatten the top of the cone until the thickness is uniform. Then use a cross-shaped sample divider to divide the sample into 4 equal parts. Discard the two diagonally opposite parts. Mix the remaining two parts again and repeat the above operation until the amount of sample that meets the experimental requirements is obtained. If the impurity ratio in the sample is higher than 5%, or there are obvious unbroken aluminum flakes or membrane fibers, and more than 30% of the particles are retained on the 75μm sieve, it is a high-impurity coarse particle sample. Weigh 3.0 g of sample and place it in a 500 mL three-necked flask. Add 20 mL of 6 mol / L dilute hydrochloric acid and 20 mL of 30 wt% hydrogen peroxide. Heat to 90 °C and keep warm for 15 min. Then, rapidly heat to 150 °C until no small decomposition bubbles are visible. Cool to 25 °C to obtain a mixture. Transfer the mixture to a 250 mL volumetric flask and make up to volume. Filter the mixture using a 0.45 μm aqueous microporous membrane to remove impurities. Collect the filtrate and transfer 10 mL of the filtrate to a 250 mL conical flask to obtain the pretreated sample solution. Add ammonia solution (V) dropwise to the conical flask containing the pretreated sample solution. 25wt%氨水 V 蒸馏水 =1:1), add while stirring at 200 r / min, and after a blue precipitate appears, add acetic acid solution dropwise (V 冰醋酸 V 蒸馏水 =1:1), continue stirring until the precipitate is completely dissolved, then add 1 mL of acetic acid solution, and add distilled water to the conical flask until the solution volume is 100 mL to obtain the acid-adjusting sample solution; Add 0.5 g of ammonium bifluoride to the acidified sample solution and stir at 200 r / min for 5 min. Then add 1.5 g of potassium iodide and immediately titrate with 0.1 mol / L sodium thiosulfate standard solution. After the solution changes from bright yellow to pale yellow, add 2.0 mL of 5 g / L starch indicator, and the solution turns blue. Continue titrating with 0.1 mol / L sodium thiosulfate standard solution until the blue color is about to disappear. Then add 10 mL of 10 wt% potassium thiocyanate solution to make it turn blue again. Continue titrating with 0.1 mol / L sodium thiosulfate standard solution until the blue color completely disappears, which is the titration endpoint. Record the amount of sodium thiosulfate standard solution consumed and calculate the copper content.

[0039] Example 7 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this embodiment and Example 6 is that the sample is 2.8g, the dilute hydrochloric acid is 18mL, the hydrogen peroxide is 18mL, the stirring temperature is 85℃ for 10min, and the temperature is kept at 90℃ for 8min. The other raw materials and preparation process are the same as in Example 6.

[0040] Example 8 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this embodiment and Example 6 is that the sample is 3.2g, the dilute hydrochloric acid is 22mL, the hydrogen peroxide is 22mL, the stirring temperature is 95℃ for 15min, and the temperature is kept at 98℃ for 10min. The other raw materials and preparation process are the same as in Example 6.

[0041] Example 9 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this embodiment and Example 6 is that the amount of potassium iodide is 1.4g, the amount of starch indicator is 1.8mL, and the amount of potassium thiocyanate is 9mL. The remaining raw materials and preparation process are the same as in Example 6.

[0042] Example 10 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this embodiment and Example 6 is that the amount of potassium iodide is 1.4g, the amount of starch indicator is 2.2mL, and the amount of potassium bisulfate is 11mL. The remaining raw materials and preparation process are the same as in Example 6.

[0043] Comparative Example 1 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this comparative example and Example 1 is that the sampling method is changed to simple random sampling, taking 0.2 g randomly from the sample pile without using the cone quartering method. The other raw materials and preparation process are the same as in Example 1.

[0044] Comparative Example 2 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this comparative example and Example 1 is that 6 mol / L dilute hydrochloric acid is replaced with an equal volume of 6 mol / L nitric acid, while the remaining raw materials and preparation process remain the same as in Example 1.

[0045] Comparative Example 3 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this comparative example and Example 1 is that 30wt% hydrogen peroxide was replaced with an equal volume of 10wt% ammonium persulfate solution, while the remaining raw materials and preparation process remained the same as in Example 1.

[0046] Comparative Example 4 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this comparative example and Example 1 is that the ammonia solution is replaced with an equal volume of 1 mol / L sodium hydroxide solution, while the remaining raw materials and preparation process are the same as in Example 1.

[0047] Comparative Example 5 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: Compared with Example 1, this comparative example differs in that the acetic acid solution is replaced with 1 mol / L sulfuric acid, while the remaining raw materials and preparation process are the same as in Example 1.

[0048] Comparative Example 6 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this comparative example and Example 1 is that ammonium bifluoride is removed, while the remaining raw materials and preparation process are the same as in Example 1.

[0049] Comparative Example 7 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this comparative example and Example 1 is that potassium iodide is replaced with an equal amount of potassium bromide, while the remaining raw materials and preparation process are the same as in Example 1.

[0050] Comparative Example 8 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this comparative example and Example 1 is that the 5 g / L starch indicator was replaced with an equal volume of 0.1 wt% phenolphthalein solution, while the remaining raw materials and preparation process remained the same as in Example 1.

[0051] Comparative Example 9 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: The difference between this comparative example and Example 1 is that the low-impurity fine particle sample was pretreated using the same pretreatment method as the high-impurity coarse particle sample, while the remaining raw materials and preparation process remained the same as in Example 1.

[0052] Comparative Example 10 A method for detecting the copper content of recovered crushed copper powder from a negative electrode includes the following steps: Compared with Example 1, this comparative example is that the high-impurity coarse particle sample is pretreated according to the pretreatment method for low-impurity coarse particle samples, while the remaining raw materials and preparation process are the same as in Example 1.

[0053] Performance testing This test uses "accuracy, precision, efficiency, and clarity of titration endpoint" as the core evaluation indicators for copper content detection. A unified standardized test procedure is adopted for Examples 1-10 and Comparative Examples 1-10 to ensure the comparability of results, as detailed below: 1. Sample Selection: Two standard negative electrode copper powder samples with known copper content were selected: a low-impurity fine-particle standard sample (standard value: Cu%=98.50%) and a high-impurity coarse-particle standard sample (standard value: Cu%=92.30%). Test Allocation: Examples 1-5 (low-impurity fine particles) and Examples 6-10 (high-impurity coarse particles) were tested with the two standard samples respectively; Comparative Examples 1-8 were tested with the two low-impurity fine-particle standard samples; in Comparative Example 9, the low-impurity sample was pretreated with high impurities and tested with the low-impurity standard sample, corresponding to Example 1; in Comparative Example 10, the high-impurity sample was pretreated with low impurities and tested with the high-impurity standard sample, corresponding to Example 6.

[0054] 2. Accuracy test: Each sample was tested 5 times in parallel using the corresponding detection method. The relative error between the single test value and the standard value was calculated (relative error = |test value - standard value| / standard value × 100%). The smaller the relative error, the higher the accuracy.

[0055] 3. Precision test: The relative standard deviation (RSD) is calculated based on the results of 5 parallel tests. RSD = (standard deviation / average value) × 100%. The smaller the RSD, the stronger the detection stability.

[0056] 4. Detection efficiency test: Start timing from the completion of sampling until the copper content is calculated, and record the total time taken for a single test. The shorter the time taken, the higher the efficiency.

[0057] 5. Evaluation of the clarity of the titration endpoint: The endpoint was blind-tested by 3 professional testers and divided into three levels: "clear (obvious color change, easy to judge), relatively clear (color change can be distinguished, requires careful observation), and blurry (color gradient, difficult to judge)". The consensus value of the 3 people's evaluation results was taken.

[0058] The formula for calculating copper content is: For a low-impurity, fine-particle sample, the copper mass fraction ω(Cu) = (V × c × M × 10) -3 ) / m×100%; For high-impurity coarse-particle samples, the copper mass fraction ω(Cu) = (V × c × M × 10) -3 ×25) / m0×100%; Where V is the volume of sodium thiosulfate standard solution consumed, c is the concentration of sodium thiosulfate standard solution (mol / L), M is the molar mass of copper 63.55 g / mol, m is the mass of the low-impurity fine particle sample (g), and m0 is the mass of the high-impurity coarse particle sample (g).

[0059] The test results are shown in Table 1.

[0060] Table 1

[0061] Accuracy and precision: Examples 1-10 of this invention all exhibit excellent accuracy and high precision, demonstrating the robustness and reliability of the method within the preset parameter range. Examples 1 and 6, as standard procedures for their respective sample types, showed the best results. Key changes in Comparative Examples 1-10 all led to a significant decrease in performance. Among them, Comparative Example 1 (uneven sampling), Comparative Example 7 (potassium iodide replaced), and Comparative Example 8 (incorrect indicator) showed the largest errors, directly proving that standardized sampling, the irreplaceability of potassium iodide, and the specificity of starch indicator are the foundation of the accuracy of this method.

[0062] Detection efficiency: Examples 1-5 (low-impurity processes) took approximately 40-45 minutes, while Examples 6-10 (high-impurity processes) took approximately 65 minutes. Comparative Example 9 (high-impurity process for low-impurity samples) took a dramatic increase in time (95 minutes), while Comparative Example 10 (low-impurity process for high-impurity samples), although shorter in time (45 minutes), showed severely inaccurate results. This strongly demonstrates the crucial role of differentiated pretreatment in improving detection efficiency while ensuring accuracy.

[0063] Titration endpoint clarity: All endpoints were rated as "clear" thanks to the optimized acidification steps (pH 3.5-4.0) and the stepwise addition of starch and potassium thiocyanate titration procedure, which effectively avoided interference from impurities and iodine adsorption, ensuring a sharp endpoint.

[0064] Most comparative endpoint evaluations were "fuzzy" or worse, especially those involving the replacement of the sample dissolution system, masking agent, redox reagent, and indicator, which directly led to difficulties in endpoint judgment and became the main source of human error.

[0065] The performance degradation of Comparative Example 1 may be due to its use of simple random sampling instead of the core conical quartering method of this invention. For solid powders such as crushed copper powder recovered from negative electrodes, which may exhibit component segregation, random sampling easily leads to the composition of the small sample being unable to represent the whole, introducing a systematic bias from the source of the detection process that cannot be corrected by subsequent analysis, thus resulting in a significant decrease in accuracy and precision.

[0066] The performance degradation in Comparative Example 2 may be due to its use of nitric acid instead of hydrochloric acid as the dissolving acid. Nitric acid is a strong oxidizing agent, which, while dissolving copper, also violently oxidizes metallic impurities such as aluminum in the sample, resulting in a large number of aluminum ions entering the solution. These additional interfering ions increase the difficulty of subsequent acid adjustment and masking, potentially affecting the stability of pH control and creating competitive interference with iodometric titration, ultimately impacting the accuracy of the results and endpoint determination.

[0067] The performance degradation in Comparative Example 3 may be due to its use of ammonium persulfate instead of hydrogen peroxide as the oxidant. Ammonium persulfate has different oxidizing properties and reaction kinetics than hydrogen peroxide, which may lead to incomplete or uneven oxidation and dissolution of copper. Furthermore, its decomposition products may introduce new ions that interfere with the pH of the system or generate bubbles, making the solution unstable and consequently resulting in a less sensitive titration endpoint and poorer repeatability.

[0068] The performance degradation of Comparative Example 4 may be due to its use of strong alkaline sodium hydroxide instead of weak alkaline ammonia for initial pH adjustment. Excessive local alkalinity of sodium hydroxide readily reacts with various ions such as copper, iron, and aluminum to form hydroxide precipitates. These precipitates may encapsulate unreacted copper or adsorb copper ions, resulting not only in losses but also potentially incomplete dissolution during subsequent acid addition, leading to lower measurement results and difficulty in identifying the endpoint due to turbidity.

[0069] The performance degradation of Comparative Example 5 may be due to its use of strong sulfuric acid instead of weak acetic acid for acidification. The addition of sulfuric acid makes it difficult to form a stable buffer system, causing the solution pH to fluctuate easily and potentially remain within the optimal range of 3.5–4.0 for iodometric titration. Uncontrolled pH can lead to incomplete cuprous iodide precipitation or accelerate the air oxidation of iodide ions, introducing additional errors and making the endpoint decolorization less pronounced.

[0070] The performance degradation of Comparative Example 6 may be due to the omission of the crucial masking agent, ammonium bifluoride. Without effective masking, impurity ions such as iron and aluminum in the sample may react with iodine ions or affect the color of the iodine-starch system, severely interfering with the stoichiometric relationship of the main reaction. This can lead to an earlier or later titration endpoint, or even abnormal color, resulting in unreliable measurement results.

[0071] The reduced performance of Comparative Example 7 may be due to its replacement of the core reagent, potassium iodide, with potassium bromide. Potassium iodide also acts as a reducing agent in the reaction (reducing Cu). 2+ Reduced to Cu + Potassium bromide plays a dual role as both a source of iodide ions and a source of iodide ions (generating I₂). Potassium bromide lacks the same reducing power and cannot initiate this crucial redox reaction, resulting in the inability to generate elemental iodine during titration. This renders the entire iodometric determination ineffective, preventing the acquisition of valid results.

[0072] The performance degradation of Comparative Example 8 may be due to its use of phenolphthalein instead of starch as an indicator. The color change range of phenolphthalein is completely incompatible with this acidic titration system, making it utterly incapable of indicating the endpoint of iodine consumption. Without the characteristic blue complex formed by starch and iodine and its subsequent fading as a basis for judgment, operators are completely unable to visually determine the titration endpoint, leading to measurement failure.

[0073] The performance degradation of Comparative Example 9 may be due to its use of a complex pretreatment process designed for high-impurity samples, which is suitable for low-impurity fine-particle samples. While this "over-processing" may ensure accuracy, it introduces unnecessary dilution, transfer, and filtration steps, which not only significantly prolongs the detection time and reduces efficiency, but also increases the risk of sample loss and contamination with each additional step, potentially slightly increasing precision error.

[0074] The performance degradation of Comparative Example 10 may be due to its incorrect use of a simplified pretreatment procedure for low-impurity samples when dealing with high-impurity, coarse-particle samples. This procedure fails to effectively dissolve, separate, or complex large amounts of impurities such as aluminum shavings and membrane fibers, resulting in a turbid final titration solution containing high concentrations of interfering ions. This "insufficient treatment" creates a complex background, severely interfering with the iodometric titration process, making endpoint determination extremely difficult, and causing the measurement results to deviate significantly from the true values.

[0075] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.

Claims

1. A method for detecting the copper content of recovered crushed copper powder from a negative electrode, characterized in that, Includes the following steps: S1. Obtain the required sample amount using the cone quartering method and distinguish the samples; S2. The sample is pretreated to obtain a pretreated sample solution; S3. Add ammonia solution to the pretreated sample solution until a blue precipitate appears, then add acetic acid solution until the precipitate dissolves, and then add 1 mL of acetic acid solution to obtain the acidified sample solution. S4. Add ammonium bifluoride and potassium iodide to the acidified sample solution in sequence, and then titrate with 0.1 mol / L sodium thiosulfate standard solution. When the solution color changes from bright yellow to pale yellow, add 5 g / L starch indicator, and the solution turns blue. Continue titrating until the blue color is about to disappear, then add 10 wt% potassium thiocyanate solution, and the solution turns blue again. Continue adding sodium thiosulfate standard solution until the blue color completely disappears, which is the titration endpoint. Record the amount of sodium thiosulfate standard solution consumed and calculate the copper content.

2. The method for detecting the copper content in the recovered crushed copper powder from the negative electrode as described in claim 1, characterized in that, The differentiation method includes the following: If the total proportion of solid impurities such as graphite, diaphragm, and aluminum particles in the sample is less than 5%, and more than 90% of the particles can pass through a 75μm standard sieve, then it is a low-impurity fine particle sample. If the impurity percentage in the sample is higher than 5%, or if there are obvious unbroken aluminum flakes or membrane fibers, and more than 30% of the particles are retained on the 75μm sieve, then it is a high-impurity coarse particle sample.

3. The method for detecting the copper content in the recovered crushed copper powder from the negative electrode as described in claim 1, characterized in that, The sample pretreatment includes the following steps: Take a low-impurity fine particle sample, add 6 mol / L dilute hydrochloric acid and 30 wt% hydrogen peroxide, heat to 80~90℃ and react for 5~10 min, then rapidly heat to 150℃ until no tiny decomposition bubbles are visible, then cool to 24~26℃.

4. The method for detecting the copper content in the recovered crushed copper powder from the negative electrode as described in claim 3, characterized in that, The ratio of the sample, dilute hydrochloric acid, and hydrogen peroxide is 0.1~0.3g: 3~5mL: 3~5mL.

5. The method for detecting the copper content in the recovered crushed copper powder from the negative electrode as described in claim 1, characterized in that, The sample pretreatment includes the following steps: Take a high-impurity coarse particle sample, add 6 mol / L dilute hydrochloric acid and 30 wt% hydrogen peroxide, heat to 85~95℃ and react for 10~15 min, then rapidly heat to 150℃ until no small decomposition bubbles are visible, cool to 24~26℃, make up to 250 mL, filter with an aqueous filter membrane and collect the filtrate, then transfer 10 mL of the filtrate to a 250 mL Erlenmeyer flask.

6. The method for detecting the copper content in the recovered crushed copper powder from the negative electrode as described in claim 5, characterized in that, The ratio of the sample, dilute hydrochloric acid, and hydrogen peroxide was 2.8~3.2g: 18~22mL: 18~22mL.

7. The method for detecting the copper content in the recovered crushed copper powder from the negative electrode as described in claim 1, characterized in that, The ammonia solution is prepared by mixing 25wt% ammonia water and distilled water at a volume ratio of 1:

1.

8. The method for detecting the copper content in the recovered crushed copper powder from the negative electrode as described in claim 1, characterized in that, The acetic acid solution was prepared by mixing glacial acetic acid and distilled water at a volume ratio of 1:

1.

9. The method for detecting the copper content in the recovered crushed copper powder from the negative electrode as described in claim 1, characterized in that, The amount of ammonium bifluoride used is 0.5g.

10. The method for detecting the copper content in the recovered crushed copper powder from the negative electrode as described in claim 1, characterized in that, The amount of potassium iodide used is 1.4~1.6g, the amount of 5g / L starch indicator used is 1.8~2.2mL, and the amount of 10wt% potassium thiocyanate solution used is 9~11mL.

Citation Information

Patent Citations

  • Method for detecting copper content in conductive slurry

    CN115598287A